Oral myofunctional and electromyographic evaluation of the anterior suprahyoid muscles and tongue thrust in patients with class II/1 malocclusion submitted to first premolar extraction - De Souza, Denize Ramirez; Semeghini, Tatiana Adamov; Kröll, Lucio Benedito; Berzin, Fausto (My University, 2007)
Objective: The aim of this study was to assess the existence of myofunctional alterations before and after first premolar extraction in Class II/1 malocclusion patients that could endanger the long-term dental arch stability. Materials and Methods: The study was performed by means of morphological, functional and electromyographic analyses in 17 Class II/1 malocclusion patients (group T) and 17 Class I malocclusion patients (group C), both groups with 12-30-year age range (mean age: 20.93 ± 4.94 years). Results: Data analyzed statistically by Student's t-test showed a significant decrease in the maxillary and mandibular dental arch perimeters after orthodontic treatment (p<0.05). The Kruskal-Wallis test analyzed data from tongue posture at rest and during swallowing, not showing significant differences after treatment (groups Tb and Ta) (p>0.05). However, group T differed significantly from group C (p<0.05). The electromyographic data showed that the anterior right and left suprahyoid muscles acted synergistically in both groups, while having a lower myoelectric activity in group T during swallowing. Conclusions: Myofunctional alterations observed after the orthodontic treatment in Class II/1 malocclusion seemed to jeopardize the long-term orthodontic stability, making recurrence possible. Further research should be conducted to compare electromyographic data before and after orthodontic treatment in order to corroborate the results of the present investigation.
Keywords: Electromyography; Malocclusion; Neck muscles; Oral myofunctional evaluation; Tongue; Tooth extractions